Functional prognosis analysis of glioma resection in the left middle precentral gyrus and posterior middle frontal gyrus - WANG Yi-jie; HU Rui-ping; ZHOU Yu-yao; LU Jun-feng (Chinese Journal of Contemporary Neurology and Neurosurgery)
Objective To investigate the functional outcomes for patients undergoing glioma resection in the left middle precentral gyrus and posterior middle frontal gyrus, and evaluate the efficacy of current surgical strategies. Methods A retrospective analysis was performed on the data of 7 patients who underwent glioma resection in the left middle precentral gyrus and posterior middle frontal gyrus in Huashan Hospital, Fudan University from January 2013 to July 2024. Preoperatively, the surgical plan was determined under the guidance of multimodal MRI navigation and reconstruction technology. Intraoperatively, awake craniotomy combined with direct electrical stimulation was employed to locate and protect functional areas. Preoperatively, the Mini-Mental State Examination (MMSE) was used to assess cognitive function, and the Aphasia Battery of Chinese (ABC) was used to evaluate language function. Postoperatively, the ABC scale was used to assess language function at 1, 3 and 6 months after surgery. Results Preoperatively, 2 cases presented with mild transcortical motor aphasia, the remaining 5 cases had normal language function. In the early postoperative period, 5 cases presented with transcortical motor aphasia, one case had mixed transcortical aphasia, and one case showed normal language function. In the long-term postoperative period, 4 cases experienced mild writing dysfunction; one case exhibited mild transcortical motor aphasia, and the other 6 cases maintained normal scores for spontaneous speech, repetition, naming, and comprehension. However, 5 cases reported that their spontaneous speech was fluent but a decrease in speech rate and coordination of articulation compared to preoperative levels was noticed, and one case felt that the auditory comprehension response time had increased. The average extent of resection was 98%, with 6 cases (6/7) achieving total resection and one case (1/7) achieving partial resection (84.05%). The median follow-up duration was 69.57 (38.00, 91.00) months, one case had tumor recurrence 74 months after operation and underwent a second surgical resection, while the remaining patients did not experience recurrence. Conclusions The combination of multimodal MRI navigation and intraoperative awake mapping with neurophysiological monitoring is crucial for optimizing functional outcomes in glioma resection within the left middle precentral gyrus and posterior middle frontal gyrus. This study highlight the critical role of this region in written language and speech motor coordination, providing important clinical evidence for the complex functions of this "non-traditional" core language area.